Focal smooth muscle proliferation in the aortic intima produced by an initiation-promotion sequence. - Majesky, M W (1985)
Human atherosclerotic fibrous plaques display a clonal character similar to many benign neoplasms. We report here that chickens treated with an initiation-promotion sequence developed focal intimal smooth muscle lesions in the thoracic aorta that resemble early forms of atherosclerosis. Scanning electron microscopy revealed small mound-like lesions protruding from an intact endothelium in birds treated with an initiating dose of 7,12-dimethylbenz[a]anthracene (Me2BA) followed by twice weekly injections of the alpha 1-selective adrenergic agonist methoxamine for 20 weeks. Intimal lesion foci were composed of densely packed modified smooth muscle cells, abundant extracellular matrix, and occasional mononuclear cells (possibly monocytes). There was no ultrastructural evidence of lipid accumulation or alteration of the underlying media. These intimal lesions appeared in aortic segments of treated chickens in a pattern similar to that observed in classical experiments of multistage tumorigenesis in epidermis and other tissues. The treatment with Me2BA followed by methoxamine produced more focal lesions per thoracic segment and more segments per group with lesions than did treatment with either Me2BA or methoxamine alone. Thoracic intimal foci were absent from untreated and vehicle-treated groups. In contrast, the growth of a spontaneously arising atheroma in the distal abdominal aorta was not demonstrably affected by the initiation-promotion regimen. Likewise, weekly injections of Me2BA for 23 weeks, while greatly enhancing abdominal atheroma growth, produced no thoracic lesions. These results provide evidence that focal proliferation of intimal smooth muscle cells, a critical early event in atherogenesis, can be produced by an initiation-promotion treatment sequence.